The epistles of Paul to the Colossians and Philemon an introduction and commentary - Carson, Herbert M. (London, UK Tyndale, 1960)
Includes bibliographical references.
Donated by Mr Alan Rowe, Emmaus student 1959-60
Keywords: Bible. N.T. Colossians -- commentaries; Bible. N.T. Philemon -- commentaries